RESEARCH OF LOCOMOTIVE MECHANICS BEHAVIOR - Tatarinova, V. A.; Kalivoda, J.; Neduzha, L. O. (Science and Transport Progress, 2018)
Purpose. The main purpose of the study is to compare and confirm the results of theoretical studies of locomotive motion along the straight and curved track sections in the set range of operating speeds, which is essential for determining their dynamic qualities. The conducted research complex is one of the prerequisites for improving the reliability of the rolling stock mechanics, in particular the bogie parameters. Methodology. The research was carried out by numerical integration of the dynamic loading of a railway vehicle using one of the modern software complexes. In this study we used the mathematical model of locomotive spatial oscillations obtained using Lagrangian equations of the second kind. Findings. Authors carried out theoretical research and performed the analysis of the vehicle behavior during the motion along the track section, which in the vertical plane has no geometric defects, and taking into account the inequalities on the example of the main locomotive. The researches were carried out both analytically and with the help of the modern software complex. Comparison of the graphs shows that the results obtained by different methods coincide with sufficient accuracy. Originality. Based on the results of many years of work, the authors present the General Classification of Locomotive Mechanics, which may be useful to researchers, who are involved in the assessment of the dynamic qualities of new and upgraded types of rolling stock. Practical value. A new licensed modern software complex has been applied, which makes it possible to use it in the design, modeling of units of rolling stock and their elements; during theoretical and experimental studies, comparison of their results. The results of theoretical research can be taken into account for the preliminary research during creating the reliable constructions of a new vehicle, further improvement of the mechanics, modernization of the existing units of rolling stock during field tests.